The Application of The Principle of Openness in Realizing Good Governance - Abdul Rauf (Jurnal Hukum Volkgeist, 2021)
The essence of good governance is a government that includes all levels of society in the design of development in a transparent and responsible, effective and fair, and ensure the implementation of the rule of law. The purpose of this research is to find out how to apply the principle of openness in realizing good governance, using normative juridical research methods, namely discussing theories and laws and regulations related to the principle of openness in the implementation of governance systems. The results showed that the application of the principle of openness in the governance system can be realized by involving the participation of the community starting from the process of policy formulation, monitoring to the evaluation of government activities or activities. The community as a mandate to the government has the right to exercise supervision or control over the administration of government. However, effective control can only be implemented if governance takes place transparently based on the principle of openness.